A quick method to assess greening in potato tubers - Brune, Sieglinde; Melo, Paulo Eduardo (Pesquisa Agropecuaria Brasileira, 2001)
In potato, both chlorophyll and glycoalkaloids syntheses are light induced, being responsible for the development of greening and a bitter taste in potato tubers, respectively. This work was carried out aiming at identifying a quick method to assess resistance to tuber greening in potato. Tubers of elite-clones, as well as of cultivars Achat (susceptible) and Bintje (resistant) were washed and visually assessed to greening (five-point scale) after 5, 10, 15, and 20 days of exposure to light (250 lux). A five-day exposure was enough to place cultivars Bintje (grade 1.0) and Achat (grade 3.0) in distinct classes. However, only after a 20-day exposure, an accurate identification of resistance sources was possible. Principal component analysis was used to group the evaluation dates. However, it did not provide a clear-cut separation of genotypes in classes of resistance to tuber greening. Taking into account the results obtained in each evaluation date, clones CNPH-036 and CNPH-065 (resistant to greening), and clones CNPH-039 and CNPH-063 (moderately, but consistently resistant) were selected. All four clones showed value per se and for breeding. Clones CNPH-009 and CNPH-019 had a variable reaction in time concerning greening and, although having value per se, are not recommended for breeding purposes.